New species of oribatid mites in the families Synichotritiidae and Phthiracaridae from Thailand, with a checklist of Thai Euptyctima (Acari: Oribatida: Euphthiracaroidea, Phthiracaroidea) - Fuangarworn, Marut; Lekprayoon, Chariya (Zootaxa, 2011)
Two new species of oribatid mites, Temburongia similanensis sp. nov. (Synichotritiidae) and Austrophthiracarus trapezoides sp. nov. (Phthiracaridae), are described based on adult specimens from leaf litter on Similan Islands, Thailand. Temburongia similanensis sp. nov. differs from T. patoi Mahunka, 1990 in having simple prodorsal and notogastral setae, one pair of median prodorsal cristae, two pairs of exobothridial setae, two longitudinal rows of ano-adanal setae, coxal setation of 3-1-2-3, tridactylous legs, and, more unusually, clusters of bothridial brachytrachea which are unknown in other synichotritiid mites. Austrophthiracarus trapezoides sp. nov. can be distinguished from the similar species A. pseudotuberculatus Mahunka, 2008 by the presence of a large trapezoid prodorsal tubercle and longer notogastral setae (seta c 1 reaching d 1 ). A checklist of Thai Euptyctima, including 19 species in four families (Oribotritiidae, Euphthiracaridae, Synichotritiidae, and Phthiracaridae), their synonyms and distributional data are presented. Plonaphacarus semiaciculatus (Mahunka, 2008) comb. nov. is proposed as a new combination for Rhacaplacarus semiaciculatus Mahunka, 2008.